Prognostic role of cardiac MRI after first episode of acute pericarditis: a long-term follow-up study. (14th October 2021) - Conte, E; Agalbato, C; Gaudenzi-Asinelli, M; Rota, A; Carollo, C; Mushtaq, S; Lauri, G; Pepi, M; Pontone, G; Andreini, D
Abstract: Introduction: Recurrent pericarditis (RP) complicates acute pericarditis in 30% of case. In this clinical setting guidelines suggest a one fits-all therapeutical approach, but only a minority of patients had RP. Pericardial LGE at cardiac MRI has been suggested as potential predictor of worse prognosis among patients with RP while no data are available regarding the role of CMR after first episode of pericarditis. Aim of the present study is to evaluate the role of cardiac MRI after a single episode of pericarditis for the identification of patients at higher risk of recurrent pericarditis that may merit more aggressive therapy. Material and methods: From a registry of consecutive patients who underwent cardiac MRI from January 2014 to January 2019 we retrospectively selected a subgroup of patients with clinical diagnosis of pericarditis according ESC guidelines on pericardial disease, who underwent cardiac CMR less than 2 week after symptoms onset, for which transthoracic echocardiography and biochemical data during acute episode were available. CMR protocol included bSSFP images, T2w images and LGE in all patients. Transthoracic echocardiography was considered to be positive for pericardial disease if pericardial effusion and/or signs of pericardial constriction were present; cardiac MRI was considered to be positive for pericardial inflammation if pericardial hyperintensity signal were detected on T2w or LGE images. Clinical follow-up was recorded for a composite end-point including new episodes of recurrent pericarditis and subsequent diagnosis of chronic constrictive pericarditis Results: A total of 26 patients were included in the study. All patients presented high risk features according to ESC guidelines on pericarditis. Pericarditis etiology was unknow (idiopathic) in 22 (84.6%), related to cancer in 3 patients (11.6%) post-myocardial injury in 1 case (3.8%). In 6 patients (24%) a myopericarditis was diagnosed. According to predefined criteria 12 patients had echocardiography positive for pericardial disease (46.2%), while in 7 patients cardiac MRI was positive for pericardial inflammation (26.9%). Both echocardiography and cardiac MRI were positive in 5 patients (19.2%). At a mean follow-up of 46.2±21.2 months a total of 8 recurrent pericarditis events were recorded and 1 patient developed chronic constrictive physiology. When corrected for peak C-reactive protein values, MRI positive for pericardial inflammation [HR (95% CI) 5.5 (1.3–24.1), p=0.034] but not echocardiography positive for pericardial disease [HR (95% CI) 0.58 (0.1–2.8), p=0.507] resulted to be associated to composite end-point at follow-up. Conclusion: Cardiac MRI positive for pericardial inflammation may identify patients at higher risk for recurrent pericarditis, independently from peak C-reactive protein values, even after the first episode of acute pericarditis Funding Acknowledgement: Type of funding sources: None.